Decentralized Finance (DeFi) - Innovations and Challenges: Exploring innovations and challenges in decentralized finance (DeFi) (Blockchain Technology and Distributed Systems, 2022)
Decentralized finance (DeFi) has emerged as a transformative force in the financial industry, offering innovative solutions that challenge traditional centralized financial systems. This paper provides an in-depth analysis of the innovations and challenges within the DeFi ecosystem, focusing on decentralized exchanges (DEXs), lending platforms, and stablecoins. The research examines the key technologies underpinning DeFi, such as blockchain and smart contracts, and evaluates their impact on financial inclusion, transparency, and security. Through a comprehensive review of current DeFi projects and platforms, this paper highlights the benefits and limitations of decentralized finance and offers insights into future trends and regulatory considerations.
Keywords: Decentralized Finance; DeFi; Innovations; Challenges; Decentralized Exchanges; DEXs; Lending Platforms; Stablecoins; Blockchain; Smart Contracts; Financial Inclusion; Transparency; Security; Regulatory Considerations